Kvantově-chemické studium adsorpce v mikroporézních materiálech - Grajciar, Lukáš (2013)
Microporous materials play a crucial role in a wide range of applications in chemical engineering, chemistry, material science or lately even in medicine. Zeolites and metal- organic frameworks (MOFs) take a prominent place among them. The most important fields of applications include gas separation, purification or gas storage. A detailed understanding of adsorption properties of these materials represents a long-standing effort from experimental as well as computational chemistry community. However, ac- curate computational description of adsorption in microporous materials represents a significant challenge for computational chemists as: (i) unit cells of the crystalline mi- croporous materials are typically large, (ii) dispersion interactions are of importance, and (iii) there are metal cations, often with open-shell electronic structure, present in the framework interacting strongly and specifically with adsorbing molecules. Despite a significant progress made in theoretical description of adsorption mechanisms in both zeolites and MOFs in last decade, there is a number of applications and systems for which the commonly used computational approaches fail to provide a needed accuracy. A whole class of such systems is represented, for example, by MOFs containing tran- sition metal coordinatively...